Mechanisms of problem solving by Sang Kancil in Hikayat Sang Kancil - Abdul Rahman, Nadiatul Shakinah; Noor Muhammad, Salmah Jan (International Journal of Scientific & Technology Research, 2020)
The animal story features the characters of animals living in the jungle. Usually, this animal character is a depicted as a living being who speaks, thinks, argues and does things that are common to humans. Animal characters also face problems and conflicts with each other. Therefore, animal stories tend to portray clever characters like Sang Kancil who can think through solving problems and conflicts. To solve these problems and conflicts, the solution mechanisms such as trick and trick are use to achieve the desired goal. This paper will focus on two objectives, namely, identifying the mechanisms by which the character is are apply and analyzing the implications of the problem-solving mechanism by using character Behavior as the study data. The methodology of this paper uses qualitative methods namely library methods and data analysis. Research on the analysis showed that the animal character of Sang Kancil uses elements of flora and fauna as a mechanism for solving problems and conflicts. It also has a positive impact on every problem and conflict that is successfully resolved. Thus, through this paper, not only can we teach but also show animal intelligence in solving problems and conflicts.